Estágios de desenvolvimento econômico regional no Sul do Brasil - Eberhardt, Paulo Henrique de Cezaro (2013)
The purpose of this research was analyzing the regional economic development of Southern Brazil s microregions, comparing their evolution in the early XXI Century. The works of W. W. Rostow guide the analysis, considering that his works classify the process of economic development according to stages. The factor analysis, through the principal components analysis method, was chosen to measure the development stages, comprising the periods of 2000 and 2010. With the economic and social variables selected, the Regional Economic Development Index (IDER) was estimated. With this indicator, the microregions were classified in three different stages of development: Advanced, In Transition, and Early. The results indicated two different effects in Southern Brazil. In 2000, development archipelagoes were observed, with few microregions which locate closely to each other and presenting superior development stages, such as the West and North sections of Parana State. In 2010, the geometric form observed is a rectangle, which can be classified as development corridors , like the ones located in the East-West direction in Santa Catarina State and East-North in Parana State. The microregions classified as advanced in the beginning of XXI Century had the same characteristics: high levels of urbanization, large quantity of teachers and high levels of homicides. In 2010, the variables related to Estate action prevailed in the advanced microregions: expenses with education, health, housing, sports and social welfare. Key-words: Regional development; regional economy; brazilian economy, economic development.